Theoretically predicted and experimentally observed relaxation pathways of two heterodinuclear 3d-4f complexes - Bender, Markus; Comba, Peter; Demeshko, Serhiy; Großhauser, Michael; Müller, Dennis; Wadepohl, Hubert (Zeitschrift für anorganische und allgemeine Chemie, 2015)
The dinucleating ligand (1,4,7,10-tetraazacyclododecane-1,4,7,10-tetrayl)-tetrakis-(methylene)-tetrakis(2-methoxy-4-methylphenol), H4L, is well preorganized with an N4O2 octahedral site for a divalent transition metal ion and an O4 site (phenolates and methoxo donors, completed by added pivalates and solvent molecules) for lanthanide ions. Two 3d-4f complexes ([DyIIINiII(μ-H2L)piv2(OH2)]ClO4 and [DyIIICoII(μ-H2L)piv2(OH2)]ClO4) were prepared and fully characterized by X-ray molecular structures and electronic properties determined by ac and dc SQUID magnetometry. While the NiII based complex shows single-molecule magnetism (SMM), the CoII complex does not. With an extensive quantum-chemical analysis, this is shown to be due to a misalignment of the single ion anisotropies in the latter complex, and reasons for this are discussed.